Long-term use of adalimumab in the treatment of moderate to severe plaque psoriasis: a review of the literature - Angela Y Moore; Blakely S Richardson (Dove Medical Press, 2010)
Angela Y Moore, Blakely S RichardsonArlington Center for Dermatology, Arlington, Texas, USAAbstract: Psoriasis is a chronic T-cell-mediated inflammatory disease that primarily affects the skin and joints. Patients with moderate to severe psoriasis constitute about 30% of the psoriasis population. Treatment of this group is challenging due to the long-term side effects, toxicities and inconvenience of conventional treatments such as phototherapy, methotrexate and cyclosporine. However, recent advances in our understanding of the pathogenesis of psoriasis have led to the popular use of biologics, which offer a safer, more convenient and effective targeted therapy. Adalimumab was originally approved for treating rheumatoid arthritis. Currently, adalimumab is also approved for treatment of adult patients with moderate to severe chronic plaque psoriasis who are candidates for systemic therapy or phototherapy or when other systemic therapies are medically less appropriate. Since the onset of the use of biologics, there have been concerns over safety and efficacy when used as long-term therapy. This paper reviews all publications, posters and abstracts reporting original data on the efficacy and/or safety of adalimumab in patients treated for chronic plaque psoriasis for more than 1 year.Keywords: psoriasis, adalimumab, biologics